Improving Methods of Finding the Least Common Multiple and the Greatest Common Divisor Using Conceptual Map - Abu Aqeel, Ibrahim (Migration Letters, 2024)
In this research methods of teaching and finding of the least common multiple (LCM) and the greatest common divisor (GCD) were visited hoping to improve both using conceptual maps. The subject matter was introduced to the 22 math education students of Hebron university in 4 lectures where we divided them into 6 groups. Seven activities each of 3 pre and post introducing conceptual maps questions were included, presentations, discussions and brain storming were used notes were taken and they include problems from the real life. The questions before introducing conceptual maps showed that the majority of students used the standard methods for finding factors, multiples, common factors, and common multiples of a number. Four groups used the tables and the remaining two used the trees. After introducing conceptual maps strategy, the students concentrated on using it through trees. Through meetings and discussions some methods of teaching were presented and finding GCD and LCM using conceptual maps was observed.